2022
DOI: 10.1038/s41598-022-23766-w
|View full text |Cite
|
Sign up to set email alerts
|

AndroMalPack: enhancing the ML-based malware classification by detection and removal of repacked apps for Android systems

Abstract: Due to the widespread usage of Android smartphones in the present era, Android malware has become a grave security concern. The research community relies on publicly available datasets to keep pace with evolving malware. However, a plethora of apps in those datasets are mere clones of previously identified malware. The reason is that instead of creating novel versions, malware authors generally repack existing malicious applications to create malware clones with minimal effort and expense. This paper investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…At present, the dataset comprises more than 21 million unique APKs, each of which has either undergone or will undergo scrutiny by several antivirus engines to ascertain which ones are classified as malicious software. To detect potential malware, the applications included in the AndroZoo dataset are analysed and categorized by employing more than 60 antivirus tools [19]. However, the AndroZoo dataset lacks explicit static features, requiring researchers to extract the features themselves.…”
Section: Androzoo Datasetmentioning
confidence: 99%
See 3 more Smart Citations
“…At present, the dataset comprises more than 21 million unique APKs, each of which has either undergone or will undergo scrutiny by several antivirus engines to ascertain which ones are classified as malicious software. To detect potential malware, the applications included in the AndroZoo dataset are analysed and categorized by employing more than 60 antivirus tools [19]. However, the AndroZoo dataset lacks explicit static features, requiring researchers to extract the features themselves.…”
Section: Androzoo Datasetmentioning
confidence: 99%
“…Sequences of Dalvik bytecode opcodes, Java VM-type signatures, the values of constant-string instructions, and signatures are a few examples of the parts that make up the characteristics that are contained. Rafiq et al [19], investigated AMD dataset and found that 29.8% applications in the AMD are repacked malware.…”
Section: The Amd Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…Elect.Crime Investigation 7(4):IJECI MS.ID-02 (2023) A Comparative Analysis of Malware Detection Methods Traditional vs. Machine Learning malicious software. Malware threats have increased due to the global adoption of cloud computing and Internet of Things (IoT) [1]. Such malicious actions have the potential to compromise the integrity, confidentiality, or availability of mobile systems [2].…”
Section: Introductionmentioning
confidence: 99%